Study protocol for using a smartphone application to investigate speech biomarkers of Parkinson’s disease and other synucleinopathies: SMARTSPEECH - Jan Rusz; Tomáš Kouba; Vojtěch Illner (BMJ Open)
Introduction Early identification of Parkinson’s disease (PD) in its prodromal stage has fundamental implications for the future development of neuroprotective therapies. However, no sufficiently accurate biomarkers of prodromal PD are currently available to facilitate early identification. The vocal assessment of patients with isolated rapid eye movement sleep behaviour disorder (iRBD) and PD appears to have intriguing potential as a diagnostic and progressive biomarker of PD and related synucleinopathies.Methods and analysis Speech patterns in the spontaneous speech of iRBD, early PD and control participants’ voice calls will be collected from data acquired via a developed smartphone application over a period of 2 years. A significant increase in several aspects of PD-related speech disorders is expected, and is anticipated to reflect the underlying neurodegeneration processes.Ethics and dissemination The study has been approved by the Ethics Committee of the General University Hospital in Prague, Czech Republic and all the participants will provide written, informed consent prior to their inclusion in the research. The application satisfies the General Data Protection Regulation law requirements of the European Union. The study findings will be published in peer-reviewed journals and presented at international scientific conferences.